Design of an Online Sales Information System using a Pre-order System for Mochicrush ID in Jambi City Based on Web - Erola, Chori; Irawan, Beni; Meisak, Despita (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
Mochicrush ID is an individual business engaged in selling food, specifically mochi, using a pre-order system. Promotion is conducted through Instagram; however, order recording often faces challenges as it is still done manually using books or mobile phones, which risks lost records and calculation errors. This issue affects the accuracy of sales information and can hinder overall business operations. This study aims to design an efficient and integrated system to manage sales transactions and pre-order processes via a web-based platform to improve the order recording and processing. The system is developed using the Laravel framework and MySQL database with the Waterfall software development method. The resulting system is expected to minimize errors in order recording, increase operational efficiency, and simplify the management of orders for the business owner. With the implementation of this computerized system, the operational performance of Mochicrush ID can be enhanced, ultimately contributing to improved customer satisfaction.